"Liturgy as a Practical Cosmology: Jenkins and Lonergan in Conversation". (15th May 2020) - Briola, Lucas
Abstract: This article introduces Bernard Lonergan to environmental ethics through a conversation with Willis Jenkins. Jenkins represents a ripe dialogue partner for Lonergan because of his attentiveness to methodological questions within environmental ethics, as in his incisive critique of Lynn White's influence. To pursue this conversation, this article examines Jenkins's critique of White and then turns to Lonergan's thought to supplement and refine this critique. From this engagement, the article identifies the need for a "practical cosmology": an ongoing Christian practice that can affectively motivate care for creation. It proposes that the Christian liturgy, through its rich symbolism and distinct cosmology, offers one such practice and thus can weave that care seamlessly within Christian identity. To test this conclusion, the article briefly considers the import of this conversation for contemporary ecclesial responses to the ecological crisis, such as in Laudato si' .